MODEM AUTOMATION OF ACCOUNTING AT RUP «BMZ» WITH APPLICATION OF 2D-SCAIMERS - A. U. Gapanuk (Литьë и металлургия)
The example of independent realization of the products accounting system at the area ASUTP of tube-rolling shop of RUP «BMZ» is given.